Associations of Plasma Nitrite, L-Arginine and Asymmetric Dimethylarginine With Morbidity and Mortality in Patients With Necrotizing Soft Tissue Infections. Issue 6 (June 2018) - Hansen, Marco B.; Rasmussen, Lars S.; Garred, Peter; Pilely, Katrine; Wahl, Anna M.; Perner, Anders; Madsen, Martin B.; Hedegaard, Elise R.; Simonsen, Ulf; Hyldegaard, Ole
ABSTRACT: Background: The nitric oxide system could play an important role in the pathophysiology related to necrotizing soft tissue infection (NSTI). Accordingly, we investigated the association between plasma nitrite level at admission and the presence of septic shock in patients with NSTI. We also evaluated the association between nitrite, asymmetric dimethylarginine (ADMA), L-arginine, L-arginine/ADMA ratio, and outcome. Methods: We analyzed plasma from 141 NSTI patients taken upon hospital admission. The severity of NSTI was assessed by the presence of septic shock, Simplified Acute Physiology Score (SAPS) II, Sepsis-Related Organ Failure Assessment (SOFA) score, use of renal replacement therapy (RRT), amputation, and 28-day mortality. Results: No difference in nitrite levels was found between patients with and without septic shock (median 0.82 μmol/L [interquartile range (IQR) 0.41–1.21] vs. 0.87 μmol/L (0.62–1.24), P  = 0.25). ADMA level was higher in patients in need of RRT (0.64 μmol/L (IQR 0.47–0.90) vs. (0.52 μmol/L (0.34–0.70), P  = 0.028), and ADMA levels correlated positively with SAPS II (rho = 0.32, P  = 0.0002) and SOFA scores (rho = 0.22, P  = 0.01). In a logistic regression analysis, an L-arginine/ADMA ratio below 101.59 was independently associated with 28-day mortality, odds ratio 6.03 (95% confidence interval, 1.41–25.84), P  = 0.016. None of the other analyses indicated differences in the NO system based on differences in disease severity. Conclusions: In patients with NSTI, we found no difference in baseline nitrite levels according to septic shock. High baseline ADMA level was associated with the use of RRT and patients with a low baseline L-arginine/ADMA ratio were at higher risk of dying within 28 days after hospital admission.